# Feromagnet question

1. Aug 6, 2010

### Petar Mali

1. The problem statement, all variables and given/known data
How from

$$(\hbar\omega-h)G_{f,f'}(\omega)=i2\langle\hat{S}_f^z\rangle\delta_{f,f'}+\langle\hat{S}^z\rangle\sum_gI(f-g)\{G_{f,f'}(\omega)-G_{g,f'}(\omega)\}$$

get

$$G_{q}(\omega)=\frac{i\hbar}{2\pi}\frac{2\langle\hat{S}^z\rangle}{\hbar\omega-h-\epsilon(q)}$$

where

$$G_{f,f'}(\omega)=\frac{1}{N}\sum_{\vec{q}} e^{i\vec{q}(\vec{f}-\vec{f'})}G_{\vec{q}}(\omega)$$

$$\delta_{f,f'}=\frac{1}{N}\sum_{q}e^{i\vec{q}(\vec{f}-\vec{f'})}$$

2. Relevant equations

3. The attempt at a solution

I really don't have a clue what to do. $$h$$ is constant.

If I use that spin don't depands of indices

$$\langle\hat{S}^z\rangle=\langle\hat{S}_g^z\rangle=S\sigma$$

and use

$$(\hbar\omega-h)\frac{1}{N}\sum_{\vec{q}} e^{i\vec{q}(\vec{f}-\vec{f'})}G_{\vec{q}}(\omega)=i2S\sigma\frac{1}{N}\sum_{q}e^{i\vec{q}(\vec{f}-\vec{f'})}+S\sigma\sum_gI(f-g)\{\frac{1}{N}\sum_{\vec{q}} e^{i\vec{q}(\vec{f}-\vec{f'})}G_{\vec{q}}(\omega)-\frac{1}{N}\sum_{\vec{q}} e^{i\vec{q}(\vec{g}-\vec{f'})}G_{\vec{q}}(\omega)\}$$

What now?

Last edited: Aug 6, 2010
2. Aug 6, 2010

### nrqed

What is the definition of I(f-g) ? We need that to make any progress.

3. Aug 6, 2010

### Petar Mali

$$I$$ is exchange interraction!

$$\sum_f I(f)e^{-i\vec{g}\cdot\vec{f}}=J(\vec{q})$$

$$\sum_g I(f-g)=\sum_{\vec{\lambda}}I(\vec{\lambda})=J(0)\equiv J_0$$

4. Aug 8, 2010

Any idea?